2019
DOI: 10.1186/s12917-019-1865-1
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography and magnetic resonance imaging study of a normal tarsal joint in a Bengal tiger (Panthera tigris)

Abstract: Background In this research, using computed tomography (CT) and magnetic resonance imaging (MRI), we provide a thorough description of the standard appearance of a right tarsal joint in a Bengal tiger ( Panthera tigris ). CT scans were performed using a bone and soft tissue window setting, and three-dimensional surface reconstructed CT images were obtained. The MRI protocol was based on the use of Spin-echo (SE) T1-weighted and Gradient-echo (GE) STIR T2-weighted pulse s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…CT and MRI allow radiologists to gauge the extent of injury, identify culprit cofactors of disease predisposition, and provide valuable preoperative information in cases that require surgical repair [ 12 ]. Effective use and interpretation of information gained by CT and MRI for diagnosis of pathological changes necessitates a thorough understanding of the normal CT and MRI imaging appearance of soft tissues and osseous structures of the region of interest [ 13 ]. To the authors’ knowledge, the CT and MRI of the bovine carpal joint have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…CT and MRI allow radiologists to gauge the extent of injury, identify culprit cofactors of disease predisposition, and provide valuable preoperative information in cases that require surgical repair [ 12 ]. Effective use and interpretation of information gained by CT and MRI for diagnosis of pathological changes necessitates a thorough understanding of the normal CT and MRI imaging appearance of soft tissues and osseous structures of the region of interest [ 13 ]. To the authors’ knowledge, the CT and MRI of the bovine carpal joint have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, excellent discrimination of the main components of the encephalon , including the rhinencephalon , telencephalon , diencephalon , mesencephalon , metencephalon , and myelencephalon , was achieved with the T2W images. These images have proven to be useful for anatomical and clinical studies of various exotic species [ 3 , 12 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Therefore, the transverse T2W images revealed the olfactory bulb and its recess, which was hyperattenuated compared to the telencephalon .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the author's knowledge, this is the first description of the head of this species using a high-field strength magnet. This technique has already provided essential information in the assessment of the anatomical knowledge of the head and associated structures in other wildlife species, such as reptiles [51,52], rodents [53,54], terrestrial mammals [55,56], as well as different avian species, including red kite (Milvus milvus), common buzzard (Buteo buteo), and common kestrel (Falco tinnunculus) [33], domestic pigeon (Columba livia domestica) [41] or African grey parrot (Psittacus erithacus) [39], among others. In contrast to conventional imaging procedures, MRI can be used to obtain images via various anatomic planes without repositioning specimens [51,[57][58][59].…”
Section: Discussionmentioning
confidence: 99%